Artificial Intelligence Based Instructional Curriculum Design - Rayhan Muhamad Ridwan; Isop Syafei (UIN Sunan Gunung Djati Bandung, 2025)
The curriculum is one of the main components in education that acts as a guideline in organizing learning in order to achieve educational goals. The curriculum regulates the entire educational process, from planning to evaluation. This study aims to discuss the design of an AI-based instructional curriculum. The method used is qualitative research with a library research approach, namely reviewing various literature related to curriculum development. The results of the study indicate that the development of technology, especially AI, can be optimized in the design of an instructional curriculum to achieve predetermined learning goals efficiently. AI can support personalized learning, automate administrative tasks, and provide data-driven insights that help educators make more informed decisions. Integrating AI into curriculum design also encourages the development of digital competencies among students and teachers, fostering innovation and adaptability in educational environments. Therefore, collaboration between educators, technologists, and policymakers is essential to ensure the effective implementation of AI in instructional design. This integration has the potential to transform conventional learning systems into more adaptive and responsive educational models.